PENEGAKAN HUKUM TERHADAP PENGEMUDI SEPEDA MOTOR YANG MENGGUNAKAN HANDPHONE PADA SAAT BERKENDARA DI KECAMATAN RUMBAI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Utama, Andrew Shandy; Rizana, Rizana; Pratiwi Susanty, Ade; Iqsandri, Rai (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on Article 106 Paragraph (1) of Law Number 22 of 2009, it is regulated that everyone who drives a motorized vehicle on the road is required to drive their vehicle reasonably and with full concentration. This type of research is Sociological Legal Research. Law enforcement against motorcyclists who use mobile phones while driving in Rumbai District based on Law Number 22 of 2009 has not been running optimally because from research observations conducted on several main roads in Rumbai District, namely Jalan Sekolah, Jalan Yos Sudarso, and Jalan Sembilang, researchers saw directly that there were 10 motorcyclists in 1 day who used mobile phones while driving on the road. The obstacle from the side of the motorcyclist is the lack of legal awareness of motorcyclists in driving on the road, while from the police side is the lack of supervision carried out by the Pekanbaru Police Traffic Unit against traffic violations in Rumbai District. Efforts made to overcome these obstacles are that the Traffic Unit of the Rumbai Pesisir Police can provide socialization of Law Number 22 of 2009 to motorcycle drivers in Rumbai District and the Pekanbaru Police Traffic Unit can increase supervision in Rumbai District and enforce the law against motorcycle drivers who use cellphones while driving on the road.Keywords: Motorcycle Driver, Handphone, Law Enforcement